If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2t-1)/3=(3t+2)/15
We move all terms to the left:
(2t-1)/3-((3t+2)/15)=0
We calculate fractions
2t/()+(-((3t+2)*3)/()=0
We calculate terms in parentheses: +(-((3t+2)*3)/(), so:We get rid of parentheses
-((3t+2)*3)/(
We multiply all the terms by the denominator
-((3t+2)*3)
We calculate terms in parentheses: -((3t+2)*3), so:We get rid of parentheses
(3t+2)*3
We multiply parentheses
9t+6
Back to the equation:
-(9t+6)
-9t-6
Back to the equation:
+(-9t-6)
2t/()-9t-6=0
We multiply all the terms by the denominator
2t-9t*()-6*()=0
We add all the numbers together, and all the variables
2t-9t*()=0
| 9(x-1)-9=6x+3(-5+x) | | 6x+7=-6+4x+21 | | -31=3v+9-8v= | | 1/5x=85 | | x2/3=90 | | 11.2d-12.72=13.6d | | -5(3x-3)+9x=6(x+4) | | 7x-6=-7+8 | | x1+x+2+x+3=45 | | 8(x-6)=-3(6-2x)+5x | | 4r-5=90 | | 40+1.50x=30 | | 12x+13=2x+93 | | 9-4(2x-1)=1-5x | | 27-7b=-6-2(1+6b) | | 42+x=-1 | | 703x+10=100 | | 3x+1/6-3x+1/42=7 | | -10x-(-5-3x=-3(4x-2) | | 4m+6=71 | | p−839=1 | | 2x-6x=-3-2-2 | | -20-8+10c=13c+20 | | x(3x+4)(x-7)=0 | | −35y−8=−33y+22 | | 7x+16+8x+12+9x+8=0 | | .10x+x=136000 | | 12x+13=2x+8+85 | | 5x–12=122 | | 7/8y-4=9 | | b+7-4bb=3 | | –6j=5−6j |